The association of the PTPN22 620W polymorphism with Behçet's disease. Issue 11 (27th July 2007) - Baranathan, Vijay; Stanford, Miles R; Vaughan, Robert W; Kondeatis, Elli; Graham, Elizabeth; Fortune, Farida; Madanat, Wafa; Kanawati, Charlie; Ghabra, Marwen; Murray, Philip I; Wallace, Graham R
Abstract : Objectives: A single nucleotide polymorphism (SNP) of the gene encoding protein tyrosine phosphatase type 22 (PTPN22 620W) has recently been described as a strong common genetic risk factor for human autoimmune disease. We have analysed the association of PTPN22 620W in patients with Behçet's disease (BD). Methods: Genomic DNA was obtained from 270 patients with BD from the UK and the Middle East. Normal controls ( n = 203) were collected from the same populations. Patients with idiopathic retinal vasculitis from the UK ( n = 136) were used as disease controls. PTPN22 620W was detected by SSP–PCR analysis and agarose gel electrophoresis. Results: The results showed an inverse correlation between the presence of PTPN22 620W and Behçet's disease in either patient group tested. There was a greatly reduced prevalence in Middle Eastern compared to UK patients and controls. Finally, there was no association with either UK patients with retinal vasculitis compared with UK controls. Conclusions: The presence of PTPN22 620W was inversely associated with BD and the distribution of the SNP in the Middle East supports previous findings in the global prevalence.